Clinicopathological investigation of steatohepatitic hepatocellular carcinoma: A multicenter study using immunohistochemical analysis of adenoma‐related markers. Issue 12 (15th October 2018) - Taniai, Makiko; Hashimoto, Etsuko; Tobari, Maki; Kodama, Kazuhisa; Tokushige, Katsutoshi; Yamamoto, Masakazu; Takayama, Tadatoshi; Sugitani, Masahiko; Sano, Keiji; Kondo, Fukuo; Fukusato, Toshio
Abstract : Aims: Steatohepatitic hepatocellular carcinoma (SH‐HCC) is a newly proposed concept, which shows histological features of steatohepatitis in HCC lesions, and it is strongly associated with metabolic syndrome (MS) and steatosis/steatohepatitis in non‐cancerous lesions. Recently, a substantial number of HCC associated with MS were reported to have developed from pre‐existing inflammatory hepatocellular adenoma (HCA). To elucidate the characteristic features of SH‐HCC, we clinicopathologically investigated strictly diagnosed SH‐HCC and non‐SH‐HCC (standard HCC). Methods: This was a retrospective multicenter study. A clinicopathological investigation was undertaken to compare 62 cases with SH‐HCC features to 31 age‐ and sex‐matched standard HCC cases, including an immunohistochemical study using markers for classification of HCA and diagnosis of HCC. Results: The characteristic features of SH‐HCC compared with standard HCC include a higher rate of complications of MS, more frequent non‐alcoholic fatty liver disease as an underlying liver disease, and HCC development in non‐cirrhotic liver. The rate of solitary tumors showed no difference between the two groups, but the median diameter of the main tumor was greater in SH‐HCCs (45 mm/20 mm, P  = 0.01). The HCCs were mostly moderately differentiated, and the patterns were mainly trabecular in both groups. Positive findings for serum amyloid A and C‐reactive proteins, classification markers of inflammatory HCA, were significantly higher in cancerous lesions of SH‐HCC cases (50%/13%, P  < 0.01 and 42%/16%, respectively; P  = 0.01). Conclusions: We confirmed that SH‐HCC was strongly associated with MS and NAFLD, and found that classification markers of inflammatory HCA were significantly higher in SH‐HCC. Further studies are needed to elucidate the relationship between SH‐CCC and HCA for understanding the carcinogenic pathways in these diseases.